Nature of the Renal Concentrating Defect in Sickle Cell Disease - Fred E. Hatch; James W. Culbertson; Lemuel W. Diggs (The Journal of Clinical Investigation, 1967)
Free water reabsorption (TcH2O) measured during 10% mannitol diuresis and subsequently during 3% saline diuresis was compared in patients with sickle cell anemia and in normal subjects. During mannitol infusion, TcH2O progressively rose with increasing osmolar clearance (Cosm) and reached a maximal level in both groups studied. During hypertonic saline diuresis, TcH2O progressively rose in the normal subjects and exceeded the maximal levels attained during mannitol diuresis, with no evidence of a maximal TcH2O level appearing. In contrast, none of the saline curves significantly exceeded the mannitol curves in the sickle cell patients but tended to parallel the mannitol curves at comparable rates of solute clearance. Since TcH2O is an index of both solute (sodium) transport from the loop of Henle and solute accumulation in the hypertonic medullary interstitium, tubular sodium handling was examined in both sickle cell patients and control subjects alike. No difference in the tubular transport of sodium could be demonstrated either under conditions of sodium loading or under conditions in which the tubular sodium load was low (water diuresis). These data support the conclusion that the defect in urinary concentration in sickle cell patients is caused by a limitation in maintaining a high concentration of solute in the medullary interstitium, thus limiting the rate of TcH2O from the collecting duct.